Evaluating Artificial Intelligence Anxiety Among Pre-Service Teachers in University Teacher Education Programs - Oluwanife Falebita (MASI Mandiri Edukasi, 2025)
Adopting artificial intelligence (AI) in education for various purposes has become prominent and has raised many user concerns. The concerns, apprehension, or fear that comes with the use of AI are referred to as Artificial Intelligence Anxiety (AI anxiety). Undergraduates are the most frequent users of AI in higher education. This study assessed AI anxiety among pre-service teachers. A survey conducted online was used for data collection. A sample of 1067 pre-service teachers in mathematics, science, and technology teacher education programs were purposefully selected for the study. A questionnaire was used to collect data regarding the pre-service teachers' AI-Anxiety in six dimensions: technology intimidation, societal impact, job displacement, technological dependence, technological dread, and ethical concerns. The instrument was hosted online through Google Forms, and the data gathered was analyzed descriptively (percentage, mean, and standard deviation) and inferentially (ANOVA and regression analysis). This study reveals a moderate level of AI anxiety among pre-service teachers. Levels of AI anxiety vary across the six dimensions, with five found to be high while only one was found to be at moderate level. It also found significant variations in the level of AI anxiety among pre-service teachers based on their area of speciality. Also, the study identified no significant influences of demographic characteristics on the level of AI anxiety among pre-service teachers, emphasizing gender. Thus, educators and institutions should urgently embark on AI literacy to improve the ethical use of AI technologies among pre-service teachers and ameliorate AI anxiety.